The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41524-020-00476-3
|View full text |Cite
|
Sign up to set email alerts
|

Band degeneracy enhanced thermoelectric performance in layered oxyselenides by first-principles calculations

Abstract: Band degeneracy is effective in optimizing the power factors of thermoelectric (TE) materials by enhancing the Seebeck coefficients. In this study, we demonstrate this effect in model systems of layered oxyselenide family by the density functional theory (DFT) combined with semi-classical Boltzmann transport theory. TE transport performance of layered LaCuOSe and BiCuOSe are fully compared. The results show that due to the larger electrical conductivities caused by longer electron relaxation times, the n-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 78 publications
7
79
0
Order By: Relevance
“…Here we take into account the intrinsic electron scattering of selenium, which with carrier mainly interacts with the longitudinal acoustic phonon. , Under this theory, relaxation time can be estimated by the following formula: where the deformation potential constant E 1 = Δ E /(Δ a / a 0 ), in which Δ E is the variation of band edge position with the lattice dilation of Δ a / a 0 . The energies of band extremum are calculated with respect to the deep core energy level of the Se atom and reasonably assume that its position is not influenced by small lattice deformation. E and V 0 in the formula of elastic modulus C = ∂ 2 E /[ V 0 ∂(Δ a / a 0 ) 2 ] are total energy and volume, respectively. From Table we see for t-Se, x / y -directional elastic constants are much smaller than that parallel to chain direction, while it is about two times of that along z -direction for r-Se, which are consistent with their structure characters.…”
Section: Resultsmentioning
confidence: 99%
“…Here we take into account the intrinsic electron scattering of selenium, which with carrier mainly interacts with the longitudinal acoustic phonon. , Under this theory, relaxation time can be estimated by the following formula: where the deformation potential constant E 1 = Δ E /(Δ a / a 0 ), in which Δ E is the variation of band edge position with the lattice dilation of Δ a / a 0 . The energies of band extremum are calculated with respect to the deep core energy level of the Se atom and reasonably assume that its position is not influenced by small lattice deformation. E and V 0 in the formula of elastic modulus C = ∂ 2 E /[ V 0 ∂(Δ a / a 0 ) 2 ] are total energy and volume, respectively. From Table we see for t-Se, x / y -directional elastic constants are much smaller than that parallel to chain direction, while it is about two times of that along z -direction for r-Se, which are consistent with their structure characters.…”
Section: Resultsmentioning
confidence: 99%
“…A high ZT via the resonant-state formation has already been discussed. The “optimal figure of merit” ( ZT optimal ) depends on “Thermoelectric quality factor” ( B ), where 70,71,74,82 The DOS effective mass can be expressed as, Where, N V -is the band degeneracy, -is the band effective mass and with m 1 , m 2 and m 3 as mass components along three principal axes in a 3D bulk sample. In an isotropic band and Here is called inertial effective mass and expressed by the given relation, 32 So, we can see that large can arise due to either a large number of conducting bands ( N V ) or by flat bands (with high ).…”
Section: Enhancement Of Power Factor (Pf)mentioning
confidence: 99%
“…So, higher or flatter bands are beneficial to improve the Seebeck coefficient. If, the charge transport by acoustic phonon is dominant, then So using isotropic band approximation, we get 70,71,74,82–94 Thus, it can be concluded that heavy band effective mass harms TE performance as it reduces mobility and hence ZT . Pei et al 75 synthesized La- and I-doped PbTe by the melting, quenching, annealing, and hot pressing methods.…”
Section: Enhancement Of Power Factor (Pf)mentioning
confidence: 99%
“…Layered material, such as thallium oxygen, bismuth oxygen selenide, and tin chalcogenide, show great promise in thermoelectric applications due to the intrinsic low lattice thermal conductivity with phonon anharmonicity generated by the interaction between adjacent layers [3][4][5][6]. Since the discovery of excellent thermoelectric performance of singlecrystal SnSe [7], the thermoelectric properties of nontoxic, earth-abundant group IV-VI have attracted special attention [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%